Psychedelics as a treatment for patients with post-traumatic stress disorder (PTSD) - Marcinkowski, Krzysztof; Mazur, Agata; Madera, Magdalena; Mazur, Sylwia; Strus, Karolina; Bizan, Aleksy; Nagórska, Emilia; Zdunek, Roksana; Dąbrowska, Natalia; Kublińska, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Post-traumatic stress disorder is a psychiatric condition following an extreme event that causes a near death of an involved individual. Since conventional treatments using selective serotonin reuptake inhibitors do not consistently yield therapeutic success, alternative substances are being explored as potential solutions. This study aims to compile information regarding the outcomes of utilizing psychedelics in individuals diagnosed with PTSD. Brief description of the state of knowledge: In July 2023, after a number of clinical trials and 20-year-long efforts to overturn the impact of a prohibition, Australia became the first country to allow doctors, in clinical development and under strict control, to use the 3,4-methyl​enedioxy​methamphetamine (MDMA) commonly known as ecstasy, as well as psylocybin in patients with post-traumatic stress disorder or depression [8]. There is a noticeable annual growth of inquiries on PubMed involving the keywords "psychedelics" and "therapeutic", amounting to 92 in 2000 and topped by 738 searches in 2023, whereas the total number of results consists of 8415 positions. Therapeutic effects of psychedelics are becoming more recognized over time. Summary: Post-Traumatic Stress Disorder (PTSD) is a complex condition that affects both the psychological and somatic aspects of the body. Thus, a multidimensional intervention is indicated. The use of psychedelics might contribute to improvements not only in the severity of PTSD but also in depression or pain. Further research on a larger group of participants should be carried out to assess the potential role of psychedelics in conventional medicine in the future, alongside psychotherapy.